Foods for the Gods: Exploring the role of foods as ceremonial and religious offerings in the island of Bali, Indonesia - Reggie Surya; Felicia Tedjakusuma (jurnal1, 2026)
Bali, the only Hindu-majority province in Muslim-majority Indonesia, has a unique tradition strongly founded on religious and spiritual values. The importance of religion among Balinese is reflected in various religious ceremonies, during which are presented beautiful and colorful offerings made of local crops and Balinese ethnic foods. This review aims to explore the use of food as offering in Balinese religious ceremonies, as well as its philosophical values. Fruits, traditional cakes (sanganan or jaja), and Balinese traditional cuisine are incorporated in numerous kinds of Balinese offerings, including canang sari, jotan (saiban), and penjor. Even though each offering has its unique characteristic and the same food might contribute to different values in different types of offerings, the use of food in religious offerings is in general an expression of gratitude and an action of giving back to nature and the gods. The elements of an offering are carefully arranged to represent certain philosophical values or specific God manifestations in Balinese Hinduism known as Nawa Dewata, the nine names of God manifestations ruling in the nine different directions. Some food offerings are also presented to the demons. In Bali, food is strongly intertwined with faith and culture. Therefore, studying the use and the value of food in Balinese ceremonial offerings would help to understand Balinese culture and tradition in a thorough manner.